Seismic Protection with Base Isolation Method Using ETABS (International Journal of Innovative Research in Computer Science & Technology, 2022)
Base isolation is one of the most  promising alternatives among the structure control  methods. In recent decades, base isolation has been  seriously considered for civil structures, such as buildings  and bridges, subjected to ground motion. Seismic  isolation technique had been applied successfully abroad,  especially in Japan, and buildings with seismic isolation  design had good performances in the earthquakes before.  Seismic isolation technique has developed well in recent  years in our country. After the Wenchuan earthquake,  some departments revised the Code for Seismic Design of  Buildings and relaxed some restraint of seismic isolation  design. Using the isolation design correctly the buildings  can get a good capability of seismic resistance. It is a  good choice for the reconstruction of the important  buildings. Focus on description of the concept of seismic  design and the design method of base-isolated structure of  Zundao CentralSchooland hospital.
Keywords: Earthquake zones; Base isolation; Seismic Forces; Finite Element; ETABS